Seawater Intrusion in the Observed Grounding Zone of Petermann Glacier Causes Extensive Retreat - Shivani Ehrenfeucht; Eric Rignot; Mathieu Morlighem (Geophysical Research Letters)
Abstract Understanding grounding line dynamics is critical for projecting glacier evolution and sea level rise. Observations from satellite radar interferometry reveal rapid grounding line migration forced by oceanic tides that are several kilometers larger than predicted by hydrostatic equilibrium, indicating the transition from grounded to floating ice is more complex than previously thought. Recent studies suggest seawater intrusion beneath grounded ice may play a role in driving rapid ice loss. Here, we investigate its impact on the evolution of Petermann Glacier, Greenland, using an ice sheet model. We compare model results with observed changes in grounding line position, velocity, and ice elevation between 2010 and 2022. We match the observed retreat, speed up, and thinning using 3‐km‐long seawater intrusion that drive peak ice melt rates of 50 m/yr; but we cannot obtain the same agreement without seawater intrusion. Including seawater intrusion in glacier modeling will increase the sensitivity to ocean warming.